The Heart of the Icefish - Bioconstruction and Adaptation - G. ZUMMO; R. ACIERNO; B. TOTA; AGNISOLA, CLAUDIO (1995)
The Channichthyidae or ''icefish'' represent an intriguing example of extreme adaptation to the stable low temperature and high oxygen content of the Antarctic waters. The lack of respiratory pigments (hemoglobin and myoglobin) in these teleosts is associated with relatively low oxygen consumption and relevant. cardio-circulatory adjustments which include large blood volume, increased relative heart weight (cardiomegaly), and very high cardiac output. The heart has the ability to displace large systolic volumes at a low rate and relatively low pressure, with large ventricular fillings (high ventricular compliance), whereas it is incapable effacing increased afterloads. These functional aspects of mechanical flexibility and restrictions of the cardiac pump have been tentatively related to some constructional aspects of the icefish cardiomegaly, particularly, at the whole ventricular level, to the trabeculate type of myo-architecture, and, at the subcellular level, to the conflict in space economy between the exceptionally high mitochondrial densities and the consequent severe reduction in myofibrillar volume. On the basis of this morphodynamic approach, we suggest that the icefish may illustrate how a certain feature (i.e., an architectural cardiac design) common to the suborder and to most teleosts, and apparently with ''irrelevant'' properties, can become useful for a specialized purpose (i.e., volume pump design); and how, in contrast, the internal machinery construction. because of structural and ultrastructural constraints, may pre;ent these stenothermal sedentary teleosts from conquering niches requiring more active locomotory habits.